2004
DOI: 10.1074/jbc.m406559200
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Functions of Jab1 Are Required for Early Embryonic Development and Growth Potential in Mice

Abstract: Jab1 interacts with a variety of signaling molecules and regulates their stability in mammalian cells. As the fifth component of the COP9 signalosome (CSN) complex, Jab1 (CSN5) plays a central role in the deneddylation of the cullin subunit of the Skp1-Cullin-F box protein ubiquitin ligase complex. In addition, a CSNindependent function of Jab1 is suggested but is less well characterized. To elucidate the function of Jab1, we targeted the Jab1 locus by homologous recombination in mouse embryonic stem cells. Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
150
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(164 citation statements)
references
References 69 publications
(105 reference statements)
12
150
2
Order By: Relevance
“…And, the cell apoptosis was arrested at G 0 /G 1 phase, which was consistent to the study of Tomoda et al in some degree (Tomoda et al, 2004). They found that Jab1-/-embryonic cells lacking other CSN components expressed comparatively higher levels of p53, p27, and cyclin E, thereby resulting in impaired proliferation and accelerated apoptosis.…”
Section: 2115 Jab1 Overexpression Enhances Chemotherapeutic Sensitivsupporting
confidence: 89%
See 1 more Smart Citation
“…And, the cell apoptosis was arrested at G 0 /G 1 phase, which was consistent to the study of Tomoda et al in some degree (Tomoda et al, 2004). They found that Jab1-/-embryonic cells lacking other CSN components expressed comparatively higher levels of p53, p27, and cyclin E, thereby resulting in impaired proliferation and accelerated apoptosis.…”
Section: 2115 Jab1 Overexpression Enhances Chemotherapeutic Sensitivsupporting
confidence: 89%
“…However, the amount of Jab1-containing small subcomplex in Jab1+/-mouse embryonic fibroblast cells was decreased, they proliferated poorly, and the cell cycle was delayed in the progression from G 0 to S phase compared with the wild-type cells. All the findings suggested that Jab1 might control cell cycle progression and cell survival via regulating multiple cell cycle signaling pathways (Tomoda et al, 2004).…”
Section: 2115 Jab1 Overexpression Enhances Chemotherapeutic Sensitivmentioning
confidence: 99%
“…11 Intracellularly, MIF complexes with the Jab1/CSN5 subunit of the COP9 signalosome, 19 which regulates numerous signaling pathways involved in gene expression and cell cycle control. [20][21][22] Several studies have indicated that activation of cell proliferation by MIF is due to a functional inactivation of the p53 tumor suppressor. 17,18,23 Thus, MIF overexpression extends the lifespan of primary cells in vitro, inhibits Myc-induced p53-dependent apoptosis, and protects macrophages from NO-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been proposed that CSN is part of a proteasome-related complex (Peng et al, 2001(Peng et al, , 2003. Regardless of its precise molecular mode of action, it can be said that CSN acts as a global regulator of Cullin-RING E3 activities and that loss of CSN function in higher eukaryotes causes severe growth defects (Freilich et al, 1999;Lykke-Andersen et al, 2003;Schwechheimer, 2004;Tomoda et al, 2004;Dohmann et al, 2005). Since it is expected that hundreds of Cullin-RING E3 functions are impaired in csn mutants, their severe phenotype may be the result of the combined defects caused by the impaired function of individual E3 activities.…”
Section: Introductionmentioning
confidence: 99%